An Integrated UUM Web-Based Electronic Ticketing Service for Express Bus Service Provider - Yeoh, Choon Hiang (2004)

(untitled)
Conventional bus ticketing transactions without IT supported are not cost-effective nowadays. With the evolution and emergence of Internet technology, there comes a new way of ticketing transaction - electronic ticketing. Internet provides this type of ticketing services available online 24-hour, day and night and anywhere as long as the ticket is still available. UUM is seen to have the ability to occupy this electronic ticketing service to its students. An integrated UUM web based electronic ticketing (UUMET) system was developed to support this idea. The UUMET system is specially designed to UUM student to enable them to make express bus ticket purchase without having to travel to the ticket counter. This project focused only to the development of a prototype for the UUMET system that support the electronic ticket buying transaction to the student of UUM. UUMET system comprises of a database that is built using MySQL database application software Apache server as the web server, and PHP as its application server. The methodology used is object -oriented system development using the Unified Modeling Language - the Unified Approach. The development of the UUMET prototype system applied all phases of the system development life cycle model namely analysis, design, prototyping and testing of the prototype system. The UUMET prototype system is tested using the scenario-based testing applying the concept of black-box strategy in a non-real life environmental.